2006
DOI: 10.1063/1.2234536
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization behavior and magnetic properties of Cu-containing Fe–Cr–Mo–Ga–P–C–B alloys

Abstract: .5 amorphous alloy is known to have good soft magnetic properties combined with large glass-forming ability. Searching for a nanocrystalline structure that could improve its magnetic properties, Cr and Mo were partially substituted by Cu. The devitrification process of Cu-containing alloys shows an additional broad crystallization event that can be described by an Avrami law, with an exponent close to unity, typical for nanocrystallization phenomena. The microstructure of the nanocrystalline alloys consists of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Once the Cu is added to the M.A., the glass transition event is not anymore clearly seen. Instead, a relatively large exothermic event, usually associated to the nanocrystallization of Cu [19] is present. For all three Cucontaining samples the crystallization takes place in two steps and finishes at a lower temperature than in the case of M.A.…”
Section: Invited Articlementioning
confidence: 98%
“…Once the Cu is added to the M.A., the glass transition event is not anymore clearly seen. Instead, a relatively large exothermic event, usually associated to the nanocrystallization of Cu [19] is present. For all three Cucontaining samples the crystallization takes place in two steps and finishes at a lower temperature than in the case of M.A.…”
Section: Invited Articlementioning
confidence: 98%
“…[19][20][21][22] Under diffusion-controlled growth, consumption of the reactants to form the primary phase results in a concentration gradient of the reactants at the crystalline/amorphous interface. If the rate of the transfer of atoms across the advancing interface is much faster than the rate of the diffusion of atoms toward the growing phase, depleted zones of the reactants form in the amorphous matrix near the interphase boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Transmission electron microscopy confirmed the amorphous character of the asquenched alloys with x + y ഛ 0.5, but alloys with x + y =1 present a small density of bcc-Fe grains, with grain sizes in the 5 -10 nm range and a crystalline volume fraction smaller than 5%, not detectable by Mossbauer spectroscopy. 20 The field dependence of magnetization was measured in a Lakeshore 7407 vibrating sample magnetometer using a maximum applied field H = 15 kOe with field steps of 50 Oe, for constant temperatures in the range of 300-625 K with increments of 10 K. Prior to the measurements, samples were stress relaxed by preannealing them at 675 K.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative method for tuning the magnetic transition temperature of an amorphous alloy consists in the addition of Mo and/or Cr. [18][19][20] In this work, the magnetocaloric effect of the FeCrMoCuGaPCB alloy series is analyzed. It will be shown that the refrigerant capacity of this series is comparable to that of a Mocontaining Finemet-type alloy with a similar Curie temperature, and is enhanced with respect to the FeCoSiAlGaPCB alloy series.…”
Section: Introductionmentioning
confidence: 99%